2023
DOI: 10.5132/eec.2022.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Brumadinho Mining Disaster: Immediate Impacts of Mine Tailings 5 Days After the Dam Rupture

Abstract: The rupture of the Córrego do Feijão Dam close to Brumadinho municipality is one of the recent and most devastating environmental disaster in Brazil. This study aims to report the results of metal determinations and acute toxicity assays of mining tailing samples collected 5 days after the dam rupture. Concentrations of As, Cu and Ni in site 1 (close to the dam); concentrations of Cu, Zn and Pb in site 2 (Solo Sagrado) and As, Cd and Cr in the three replicates of site 3 (Mario Campos municipality) were higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recently, lead (Pb) bioaccumulation has received increased concern as it has been found that Pb has no safe concentration in terms of DNA modification risk in humans; thus, even low concentration Pb exposure can lead to neurological and hematological disturbance (Araujo et al, 2021). Further, recent mining disasters in Brazil and worldwide have reinforced that it is urgent to maintain metal biomonitoring programs in vulnerable areas (Bordon et al, 2023).…”
mentioning
confidence: 99%
“…Recently, lead (Pb) bioaccumulation has received increased concern as it has been found that Pb has no safe concentration in terms of DNA modification risk in humans; thus, even low concentration Pb exposure can lead to neurological and hematological disturbance (Araujo et al, 2021). Further, recent mining disasters in Brazil and worldwide have reinforced that it is urgent to maintain metal biomonitoring programs in vulnerable areas (Bordon et al, 2023).…”
mentioning
confidence: 99%